ISLAMIC APPROACH TO THE ENVIRONMENT AND THE ROLE'S IN THE ENVIRONMENT PROTECTED - Meraj Ahmad Meraj (SCAD Independent, 2016)
The paper studies the Islamic viewpoint about the environment. Environment holds a central position in most of the discussions of development strategies in the contemporary globalizes world. This is why that deteriorating environment is adversely affecting human lives and is a potential danger for future generations. Today, the environmental crisis endangers human being, other living organism and the natural world alike. How should human behave towards the natural environment is remained most important. Technological solution has not been resulting in satisfying outcome. Discussing the role of the Islamic principles of unity, trustee and responsibility, the Quranic teachings may enhance the environmental consciousness among the people which enable them to establish friendly relationship between God, humankind and nature. In this respect, this paper is a humble attempt to understand the Islamic approach to the environment to explore various conceptual dimensions of environmental security and the possible role of Islam in protecting the environment for the broader benefit of humanity. This paper will also discuss the Islamic principles of human behavior to deal with the nature and environment.